Sejarah Keberadaan Gordang Sambilan Di Desa Taming Kabupaten Pasaman Barat - Marhabi M. Fajrin; Yensharti Yensharti (SENDRATASIK UNP, 2021)
This research aims to describe the history of the existence of Gordang Sambilan in the community in Taming village, Ranah Batahan District, West Pasaman Regency, West Sumatra Province. This type of research is qualitative with descriptive methods. The instrument of this study is the researcher himself. Data collection techniques based on library studies, observations, interviews and documentation. The data is analyzed with data reduction measures, data presentation, and conclusion. The theories used in this study are as follows. The diffusion process includes; 1) the dissemination of culture; 2) the history of the dissemination of cultural elements. Based on the results of his research found that, the history of the existence of Gordang Sambilan in Taming village began in 2004 on the proposal of Prof. Dr. Marjuni Rangkuti Mangaraja Gading Patembal professor at the University of North Sumatera who is a descendant of the king. The making of Gordang Sambilan is done in cooperation by Taming villagers with materials from Aren trees. the use of Gordang is agreed only for customary wedding ceremonies with the condition of slaughtering 2 goats. Gordang Sambilan was first used in the traditional wedding procession in 2004. The first person to teach Gordang Sambilan to the community was Named Lokot Mian. Taming village youth are enthusiastic to learn Gordang Sembilan so that this art is loved by Taming villagers until now.